Kualitas Pelayanan PT. Pertamina (Persero) Dalam Penyaluran Bahan Bakar Minyak (BBM) di Kabupaten Merauke - Andri Irawan (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
The realization of quality public services is one of the characteristics of goodgovernance as a goal of the utilization of the state apparatus. Therefore, every public andprivate organization is demanded to be able to provide quality services. This study aims todescribe and analyze the quality of service of PT. Pertamina (Persero) in distributing fuel oil(BBM) in Merauke Regency with a qualitative approach. The results showed that the qualityof fuel distribution services conducted by PT Pertamina of Merauke Regency has not fully metthe criteria of quality service. This can be seen from the service quality indicators that arerelated to responsiveness and reliability. Where in this reliability and responsiveness serviceshows the time of service hours at Pertamina, some partners are still not satisfied with thetimely service hours because there are still many factors that influence it, the ability of theapparatus, service system and service facilities which still do not provide the system servicesthat do not meet the service quality standards at Pertamina are on time, on the right amount,on the right quality.